TINGKAT KEPUASAN KONSUMEN OBAT TRADISIONAL APOTEK BARENG DI KECAMATAN KLOJEN KOTA MALANG - Aditya Ayuning Siwi, Mayang; Mardianto, Rudy (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
A pharmacy is a pharmaceutical service facility where pharmaceutical practice is carried out by pharmacists. Consumer satisfaction means that the performance of a service is at least the same as expected or exceeds what is expected. This research was conducted to determine the level of satisfaction of traditional medicine consumers at pharmacies. This research uses a non-experimental quantitative method with a descriptive approach, with a population of pharmacy consumers and 100 samples, and an accidental sampling technique. The level of consumer satisfaction can be measured using variables, reliability, responsiveness, confidence, physical evidence and empathy. Satisfaction level measurement was carried out using a questionnaire and 5 quality measurement variables. The results obtained on the variable reliability 80.07% level of satisfaction, responsiveness 80.1% level of satisfaction, confidence 74.4% level of satisfaction, empathy 78.8% level of satisfaction and tangible 73.88% satisfaction level. And an average satisfaction value of 77.45% consumer satisfaction was obtained from 5 variables, which means consumers felt satisfied